Bovine anaplasmosis and tick‐borne pathogens in cattle of the Galapagos Islands. Issue 5 (22nd March 2018) - Gioia, G. V.; Vinueza, R. L.; Marsot, M.; Devillers, E.; Cruz, M.; Petit, E.; Boulouis, H. J.; Moutailler, S.; Monroy, F.; Coello, M. A.; Gondard, M.; Bournez, L.; et al.
Summary: A cross‐sectional study was conducted to determine the species of Anaplasma spp. and estimate its prevalence in cattle of the three main cattle‐producing Galapagos Islands (Santa Cruz, San Cristóbal and Isabela) using indirect PCR assays, genetic sequencing and ELISA. Ticks were also collected from cattle and scanned for 47 tick‐borne pathogens in a 48 × 48 real‐time PCR chip. A mixed effects logistic regression was performed to identify potential risk factors explaining Anaplasma infection in cattle. A. phagocytophilum was not detected in any of the tested animals. Genetic sequencing allowed detection of A. platys ‐like strains in 11 (36.7%) of the 30 Anaplasma spp.‐positive samples analysed. A. marginale was widespread in the three islands with a global between‐herd prevalence of 100% [89; 100]95% CI and a median within‐herd prevalence of 93%. A significant association was found between A. marginale infection and age with higher odds of being positive for adults (OR = 3.3 [1.2; 9.9]95% Bootstrap CI ). All collected ticks were identified as Rhipicephalus microplus. A. marginale, Babesia bigemina, Borrelia theileri and Francisella ‐like endosymbiont were detected in tick pools. These results show that the Galapagos Islands are endemic for A. marginale .